Experimental study on fracture properties of concrete under cyclic loading using digital image correlation method. Issue 13 (28th September 2022) - Bu, Jingwu; Chen, Xudong; Guo, Shengshan; Zhang, Jinhua
Abstract: Three-point bending tests are performed on notched concrete beams under various cyclic loading regimes. Meanwhile, the digital image correlation (DIC) method is used to monitor the crack propagation. The fatigue fracture life decreases with the loading level increases for constant-amplitude cyclic loading. The residual crack mouth opening displacement (CMOD) accumulates and fracture stiffness degrades with the loading process. The size of fracture process zone (FPZ) can be determined based on the full displacement field monitored by DIC method. The length of FPZ increases linearly with the increasing of effective crack length before the crack tip opening displacement (CTOD) exceeds the critical value. When CTOD exceeds the critical value, a macroscopic crack formed in front of the initial crack tip. For cyclic envelope loading, the length of FPZ increases at beginning and then decreases with the increasing of effective crack length. For constant-amplitude loading, CTOD never reaches the critical value, and the macroscopic crack does not propagate forward. Finally, it is found that both the calculated effective crack lengths of concrete under constant-amplitude loading by two-parameter model (TPM) and DIC methods present three-stage feature, but the values calculated by TPM are smaller than those by DIC method.